Design and development of bulletproof vest using kenaf fibre embedded with x-ray films - Rayney Azmi, Ahmad Mustafa; Hameed Sultan, Mohamed Thariq; Ariffin, Ahmad Hamdan (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2017)
Existing bulletproof vests are either too heavy, or too expensive. Therefore, a more effective performance, user friendly, lighter and cheaper bulletproof vest is desired. This study discusses tensile characterization and high velocity impact testing on new materials to replace the existing insert plate for the current available bulletproof vest. The materials chosen for this research are a natural fibre, namely kenaf and x-ray film. The materials were fabricated using the traditional hand lay-up method. From the tensile characteristics, the third configuration was proposed as the best configuration.